2019
DOI: 10.1136/bmjdrc-2018-000639
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cardiovascular event and mortality in relation to refill and guideline adherence to lipid-lowering medications among patients with type 2 diabetes mellitus in Sweden

Abstract: ObjectiveTo analyze the risk of cardiovascular (CV) events and mortality in relation to adherence to lipid-lowering medications by healthcare centers and patients with type 2 diabetes mellitus (T2DM).Research design and methodsWe included 121 914 patients (12% secondary prevention) with T2DM reported by 1363 healthcare centers. Patients initiated lipid-lowering medications between July 2006 and December 2012 and were followed from cessation of the first filled supply until multidose dispensed medications, migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition, we showed that diabetes is a significant predictor for time to CV hospitalization (HR 1.43; P = 0.022), underscoring the relevance of implementing appropriate CV management in this patient population. The importance of guideline adherence in reducing CV risk in patients with T2DM was also confirmed in a Swedish study on lipid-lowering therapies, with the results demonstrating a 44-51% higher risk of CV events and a doubled risk of all-cause mortality in patients with low adherence to Swedish lipid-lowering prescribing guidelines [38], despite evidence for increased incidence of T2DM due to statin use [36]. Another U.S. claims data study estimated that 1415 major adverse cardiovascular events (MACE) could be prevented over a 3-year period by closing the gap in high-dose statin use in a cohort of patients with T2DM and ASCVD who were currently not adequately treated [34].…”
Section: Discussionmentioning
confidence: 78%
“…In addition, we showed that diabetes is a significant predictor for time to CV hospitalization (HR 1.43; P = 0.022), underscoring the relevance of implementing appropriate CV management in this patient population. The importance of guideline adherence in reducing CV risk in patients with T2DM was also confirmed in a Swedish study on lipid-lowering therapies, with the results demonstrating a 44-51% higher risk of CV events and a doubled risk of all-cause mortality in patients with low adherence to Swedish lipid-lowering prescribing guidelines [38], despite evidence for increased incidence of T2DM due to statin use [36]. Another U.S. claims data study estimated that 1415 major adverse cardiovascular events (MACE) could be prevented over a 3-year period by closing the gap in high-dose statin use in a cohort of patients with T2DM and ASCVD who were currently not adequately treated [34].…”
Section: Discussionmentioning
confidence: 78%
“…Given the established association of decreased drug compliance with negative health outcomes in chronic conditions, more research on predictors of medication persistence is needed in the context of treatment for ADPKD. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Given the established association of decreased drug compliance with negative health outcomes in chronic conditions, more research on predictors of medication persistence is needed in the context of treatment for ADPKD. 27,28 Limitations of the analysis are the post hoc nature of the analyses and the relatively small proportion of noncompleters in each trial arm (ranging from 7.7% to 23.0%). The small number of noncompleters may have decreased the power to detect differential effects of completer versus noncompleter status.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with documented CVD, the lower adherence to statin therapy has been associated with a greater mortality risk 27 . In another health care database study from Sweden, lower refill adherence to lipid‐lowering medications resulted in higher CVD mortality among patients with type 2 DM 28 . Similarly, in newly diagnosed type 2 DM patients, lower anti‐diabetic medication adherence has been associated with higher long‐term all‐cause mortality 29 .…”
Section: Discussionmentioning
confidence: 99%